Discovering UGC Communities to Drive Marketing Strategies: Leveraging Data Visualization - Ramon Saura, Jose; Reyes-Menendez, Ana; Palos-Sanchez, Pedro; Filipe, Ferrão (Journal of Tourism, Sustainability and Well-being, 2019)
The digital tourism ecosystem is changing driven by the massive use of new technologies and the increase of data generated by travelers during their trips. In this digital landscape, businesses in the tourism sector are adapting their strategies to take better advantage of new knowledge that can be extracted from the Internet, specifically from social networks. The objective of this research is to define the content strategy in social networks that businesses in the digital tourism sector should follow and to highlight the importance of new data visualization techniques for Marketing and Marketing analytics. To this end, tourist communities of Twitter users have been detected by analyzing the User Generated Content (UGC) and applying algorithms for data visualization on a sample of n = 10.00 tweets from the interactions between the UGC on Twitter and the 25 Top Hotels in the World as designated by TripAdvisor’s Travelers’ Choice Awards. A total of n = 3.158 tweets were analyzed, focusing specifically on comments that had hashtags and interactions with these hotels, with the aim of detecting communities according to the type of content shared, in order to measure the communities’ impact and influence in the digital tourism sector. The results of this research study identify the main topics related to the tourism sector and the most active communities according to their impact, which allows CEOs and managers of tourism companies to refine their marketing strategies for the digital tourism industry.